Low muscle mass and low muscle strength associate with nonalcoholic fatty liver disease. Issue 4 (April 2020) - Gan, Da; Wang, Lu; Jia, Menghan; Ru, Yuan; Ma, Yiyun; Zheng, Weifang; Zhao, Xueyin; Yang, Fei; Wang, Tianru; Mu, Yun; Zhu, Shankuan
Summary: Background: It is unclear whether low muscle mass and low muscle strength are independently or jointly associated with nonalcoholic fatty liver disease (NAFLD). Hence, the aim of the present study was to investigate the associations of NAFLD with low muscle mass, low muscle strength, sarcopenia, and sarcopenic obesity. Methods: A total of 5132 participants aged 18–80 years were recruited in this cross-sectional study. NAFLD was diagnosed using ultrasound. Muscle mass was evaluated using skeletal muscle mass index and muscle strength was evaluated using weight-adjusted hand grip strength. Sarcopenia was defined as the presence of both low muscle mass and low muscle strength. Sarcopenic obesity was defined as the presence of both sarcopenia and obesity. Multivariate logistic regression models were used to explore the associations of NAFLD with low muscle mass, low muscle strength, sarcopenia, and sarcopenic obesity. Results: Low muscle mass and low muscle strength were positively and independently associated with NAFLD (mass: odds ratio [OR], 2.57; 95% confidence interval [CI], 2.03–3.25; strength: OR, 1.47; 95% CI, 1.21–1.80). Compared with low muscle mass or low muscle strength alone, sarcopenia was associated with a higher risk of NAFLD (OR, 3.91; 95% CI, 2.90–5.28). Whether obesity was defined by body mass index (BMI) or waist circumference (WC), sarcopenic obesity was associated with a higher risk of NAFLD (BMI: OR, 10.42; 95% CI, 7.14–15.22; WC: OR, 11.64; 95% CI, 8.22–16.48) than sarcopenia or obesity alone. Conclusions: Low muscle mass and low muscle strength were positively and independently associated with NAFLD. When both were presented in the sarcopenic state, the risk of NAFLD was higher, and a concurrence of sarcopenia and obesity showed the highest risk of NAFLD.